Modeling and robust structural control design for hybrid AC/DC microgrids with general topology - Shafiee-Rad, Marjan; Sadabadi, Mahdieh S.; Shafiee, Qobad; Reza Jahed-Motlagh, Mohammad (International journal of electrical power & energy systems, 2022)
•Considering the hybrid microgrid as one electrical entity and models the interactions amongst DC, IC, and AC units.•Developing a mathematical model for islanded hybrid microgrids with general topology containing several IC units.•Proposing a non-droop-based decentralized H∞ control approach for hybrid microgrids to regulate both IC currents and PCC voltages.•Providing robust stability and desired performance under several uncertainty sources, by modeling all uncertainties as a convex polytope.•Applicability to hybrid microgrids with different configurations and number of IC units, and scalability to the size of the hybrid system. Hybrid AC/DC microgrids are designed to utilize different types of renewable energy sources, meeting the requirements of numerous kinds of loads. A hybrid microgrid consists of a DC sub-grid, an AC sub-grid, and an interfaced sub-grid. In this paper, it is assumed that the DC and AC sub-grids contain several distributed generation (DG) units with arbitrary topology, and the interfaced region consists of several bidirectional interlink converter (IC) units. In the islanded mode of hybrid microgrid operation, one of the key control objectives is to stabilize and regulate the point of common coupling (PCC) voltages of both DC and AC sub-grids and also manage the proportional power-sharing between the sub-grids. This paper proposes a modeling framework and an optimal decentralized output-feedback-based control strategy for the voltage regulation of both DC and AC sub-grids as well as the current adjustment of IC units in a hybrid AC/DC microgrid with general topology. The proposed scheme guarantees robust stability and performance of hybrid microgrids subject to different uncertainty sources. In our proposed modeling setting, the uncertainty sources including plug-and-play (PnP) functionality of DG and IC units, microgrid topology changes, loads variations, and uncertain filter parameters of IC units are modeled as a convex polytope. The control design problem for the polytopic model is converted into a multi-objective convex optimization problem with structural constraints on decision variables. Several scenarios are performed in MATLAB/Simulink to validate the effectiveness of the proposed control mechanism for hybrid AC/DC microgrids.